(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
During the studies of micromycetes-decomposers of Kapan City and its surrounding, 32 species of fungi were detected, 8 of which belong to Zygomycetes and 24 belong to Ascomycetes classes. In the studied soils there were widespread species of genus Penicillium (9), Aspergillus (8) and representatives of mucoral fungi (8 species).